Quantum Measurement Problems and Proposed Solutions - Cemil Kaya; Sevda Kara; Mohammad Ali (Yayasan Adra Karima Hubbi, 2025)
The problem of quantum measurements has become one of the most controversial topics in quantum physics. Various interpretations of the role of observers and measurement processes in the quantum world have been proposed, but there is no clear consensus yet. The study focuses on the various proposed solutions to quantum measurement problems, highlighting the theory of decoherence and Many Worlds as promising alternatives. The purpose of this study is to analyze the various proposed solutions to quantum measurement problems and explore the relevance of decoherence theory and Many Worlds in explaining measurements without directly involving observers. The method used in this study is a literature analysis of 30 leading publications that discuss the topic of quantum measurement problems and proposed solutions. The data collected included theoretical and experimental studies relevant to Copenhagen's interpretation, Many Worlds, and decoherence theory. The study found that Copenhagen's interpretation continues to dominate the literature, but approaches such as Many Worlds and decoherence are gaining more attention. Decoherence theory in particular offers a more adequate explanation for bridging the gap between the quantum world and the classical world without requiring the role of an observer in measurement. The study concludes that although many solutions have been proposed, decoherence theory provides a more cohesive and comprehensive alternative in addressing quantum measurement problems. Further research is needed to test the reliability of these theories in more controlled quantum experiments.